Evaluation of Pencak Silat Sports Achievement Coaching Program at Naga Hitam College in Semarang City (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2021)
Pencak Silat Naga Hitam college is located in Semarang, the athletes come from the elementary, juniorhigh school and senior levels, however athletes rarely included PPLOP of Central Java, whereas this college has long been established and formed. The adultlevel of this college has also minimum achievement from several competitions that have been followed. The TGR art number, athletes from Naga Hitam pencak silat college have never received medals from thechampionships that was followed. The purpose of this research is to: analyze the evaluation of Context, Input, Process and Product of the coaching achievements of the Naga Hitam college performance coaching program in Semarang. The study approach in this research used a qualitative approach. Data collection techniques used were observation, interview and documentation techniques. Data analysis were by means of data reduction, data presentation and drawing conclusions. Based on the results of the research, it can be concluded that the evaluation of the performance development program of Naga Hitam Semarang pencak silat through evaluation of context, input, process and product can be explained that the management of coaching at the Naga Hitam college in Semarang City has been going well because of a clear vision and mission so that athletes can excel, the program training is carried out quite well, funding, transport is good to support athletes to be able to achieve and seen from the targets achieved by the Semarang City Naga Hitam College as expected in participating in the championship.